2002
DOI: 10.1080/09638280110066334
|View full text |Cite
|
Sign up to set email alerts
|

Development and consumer validation of the Functional Evaluation in a Wheelchair (FEW) instrument

Abstract: The items on the FEW focus on the interaction between the consumer, the technology, and the milieu. Consumers viewed the overall importance of FEW categories for seating-mobility system users differently than when they self-administered the FEW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 3 publications
1
35
0
1
Order By: Relevance
“…Previous studies have shown that reaching is 1 of the 10 important functional tasks for an individual to perform seated in a wheelchair (18,22,23). Sprigle and colleagues (23) investigated reach in SCI subjects and the effects of differing seating cushions and backrest heights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that reaching is 1 of the 10 important functional tasks for an individual to perform seated in a wheelchair (18,22,23). Sprigle and colleagues (23) investigated reach in SCI subjects and the effects of differing seating cushions and backrest heights.…”
Section: Discussionmentioning
confidence: 99%
“…With the TLSO on, subjects were significantly slower in donning a shirt (P , 0.05), donning pants (P , 0.05), performing even-level transfers (P , 0.01), performing uneven-level transfers (P , 0.01), and propelling a wheelchair (P , 0.01). Although this study provided insight into the effects of the TLSO on timeliness of task completion, it did not study the effect of TLSO on upper extremity reaching, a task identified as important among persons using wheelchairs (18). Therefore, the purpose of this study was to quantify the effect of a TLSO on the reachable workspace volumes and reach of children with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for higher ecological validity, the evaluation process should include "field trials" in which the DSS is used by target users for extended periods of time outside the laboratory. An evaluation of the DSS in real-world settings should also evaluate the users' ability to function when using the navigation assistance from the DSS with instruments such as Functioning Everyday With a Wheelchair [30][31] or Power-Mobility Indoor Driving Assessment [32]. Further, anecdotal data obtained during the interviews will provide investigators with additional insight into specific situations that lead to system failures (collisions or software crashes), difficulties encountered when transporting the system, and problems positioning users within the chair.…”
Section: Discussionmentioning
confidence: 99%
“…While this is clearly the intent of wheelchair provision though the enablement of mobility, most existing measures of wheelchair outcomes evaluate consumers' capacity [49] rather than their performance of valued life-activities. Of the studies included in this scoping review, only one study used a measure that included Activity and Participation related items, the Function Every day in a Wheelchair Instrument (FEW) [50]. All other measures were either of consumer satisfaction, or impairments in body structures or body functions.…”
Section: Outcome Measurementmentioning
confidence: 99%